2021
DOI: 10.1186/s12864-020-07339-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with the biosynthesis of unsaturated fatty acid and oil accumulation in herbaceous peony ‘Hangshao’ (Paeonia lactiflora ‘Hangshao’) seeds based on transcriptome analysis

Abstract: Background Paeonia lactiflora ‘Hangshao’ is widely cultivated in China as a traditional Chinese medicine ‘Radix Paeoniae Alba’. Due to the abundant unsaturated fatty acids in its seed, it can also be regarded as a new oilseed plant. However, the process of the biosynthesis of unsaturated fatty acids in it has remained unknown. Therefore, transcriptome analysis is helpful to better understand the underlying molecular mechanisms. Results Five main fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 89 publications
2
18
0
Order By: Relevance
“…Biochemical and molecular research contributes to better understanding and possible regulation of developmental traits, from stress tolerance [ 60 , 61 ] to flower color [ 62 , 63 ] and biosynthesis of secondary metabolites [ 64 ]. Currently, the first priority for genetic research should be introduction of disease resistance to new cultivars, and recent reports confirm possibility of this direction [ 65 67 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Biochemical and molecular research contributes to better understanding and possible regulation of developmental traits, from stress tolerance [ 60 , 61 ] to flower color [ 62 , 63 ] and biosynthesis of secondary metabolites [ 64 ]. Currently, the first priority for genetic research should be introduction of disease resistance to new cultivars, and recent reports confirm possibility of this direction [ 65 67 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…The determination of starch content was conducted according to the instructions of plant starch content reagent kit (Shanghai Cableridge Biotechnology Co., LTD.). The extraction of crude fat was conducted according to Meng et al (2021). And the crude fat content was calculated by the following formula C f (mg/g) = 1000 × (W 1 -W 0 ) / W 2 .…”
Section: Content Determination Of Nutritious Substancesmentioning
confidence: 99%
“…Fatty acid composition analysis and content determination mainly includes the following steps such as standard solution preparation, sample hydrolysis, fat extraction, fatty acid esterification, gas chromatographic and mass spectrometric (GC-MS) parameter setting, and calculation for the fatty acid absolute content. The specific methods were referred to previous description (Meng et al, 2021).…”
Section: Fatty Acid Composition Analysis and Content Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“… Fei et al (2020) employed transcriptome sequencing and RT-qPCR to determine the expression levels of 20 genes related to fatty acid synthesis in Zanthoxylum bungeanum seeds, the results of intergroup correlation and RDA analysis suggested that ENR , ECR , and SAD1 are the key genes in fatty acid synthesis. Meng et al (2021) used transcriptomics to predict the key genes of unsaturated fatty acid (UFA) synthesis and oil accumulation in Paeonia lactiflora seeds, including MCAT , KASIII , FATA , SAD , FAD2 , FAD3 , and DGAT , providing more comprehensive genomic resources for understanding the transcription of genes in P. lactiflora seeds.…”
Section: Introductionmentioning
confidence: 99%